Solusi Numerik Persamaan Good Boussinesq Menggunakan Metode Garis - Lubis, Yunika Zultira; Arif, Salmawaty; Saputra, T. Murdani (Syiah Kuala University, 2024)
The Good Boussinesq equation is a hyperbolic partial differential equation, for which the analytical solution is generally difficult to determine thus necessitating a numerical approach. This study aims to obtain the numerical solution of the Good Boussinesq equation using the method of Lines and to calculate the accuracy of this method in solving the equation. Numerical simulation were also conducted to compare the numerical solution with the analytical solution in the form of a single soliton. Subsequently, a numerical simulation was performed to compare the numerical solution with the analytical solution in the form of a single soliton. The simulation conducted for a single soliton as an analytical solution demonstrates that the numerical solution closely approximates the analytical solution, as indicated by the nearly identical shapes and positions of the resulting wave. This is also indicated by the relatively small Root Mean Square Error (RMSE) of 1.89E-03, which shows that the Method of Lines is quite effective in solving the numerical solution of the Good Boussinesq equation based on the calculation of squared errors.